Comparison of nested PCR with immunofluorescent-antibody assay for detection of Ehrlichia canis infection in dogs treated with doxycycline. - Wen, B (1997)
A partial 16S rRNA gene was amplified in Ehrlichia canis-infected cells by nested PCR. The assay was specific and did not amplify the closely related Ehrlichia chaffeensis, Ehrlichia muris, Neorickettsia helminthoeca, and SF agent 16S rRNA genes. The assay was as sensitive as Southern hybridization, detecting as little as 0.2 pg of E. canis DNA. By this method, all blood samples from four dogs experimentally infected with E. canis were positive as early as day 4 postinoculation, which was before or at the time of seroconversion. One hundred five blood samples from dogs from Arizona and Texas (areas of E. canis endemicity) and 30 blood samples from dogs from Ohio (area of E. canis nonendemicity) were examined by nested PCR and immunofluorescent-antibody (IFA) test. Approximately 84% of dogs from Arizona and Texas had been treated with doxycycline before submission of blood specimens. Among Arizona and Texas specimens, 46 samples were PCR positive (44%) and 80 were IFA positive (76%). Forty-three of 80 IFA-positive samples (54%) were PCR positive, and 22 of 25 IFA-negative samples (88%) were negative in the nested PCR. None of the Ohio specimens were IFA positive, but 5 specimens were PCR positive (17%). Our results indicate that the nested PCR is highly sensitive and specific for detection of E. canis and may be more useful in assessing the clearance of the organisms after antibiotic therapy than IFA, especially in areas in which E. canis is endemic.